Perceptions of need-support when "having fun" meets "working hard" mentalities in the elite sport school context. Issue 1 (2nd January 2020) - Berntsen, Hedda; Kristiansen, Elsa
ABSTRACT: The aim of this study was to investigate athletes and coaches' perceptions of coach need-supportive behaviour and to increase our understanding of the athlete-coach dynamic in the endorsement process. Video-based interviews were conducted with 11 athletes and 10 coaches at an elite sport school in Norway. Narratives were used to tell the story of the predominantly hedonic athlete (the aim of sport participation is having fun) and the predominantly eudaimonic athlete (the aim of sport participation is development). There was an obvious endorsement misfit between the group of athletes labelled hedonic and their coaches. The paradox of the endorsement process intensifies when the "have fun" mentality of the athlete meets the "work hard" mentality of the coach, which, for some athletes, undermines their need-satisfaction, commitment, performance, and well-being. The findings suggest a strong need for a fit between coach and athlete aims for successful coaching in the elite sport school context.